FIGURE 4 in Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae) - Fanciulli, Pietro Paolo; Leo, Chiara; Convey, Peter; Frati, Francesco; Carapelli, Antonio (Zenodo, 2018)
FIGURE 4. Folsomotoma octooculata; scanning electron microscopy. A, Mucro; B, ClaW and empodial appendage; C, Ant. IV shoWing seVeral seta–like sensilla; D, Macrochaeta on the last abdominal tergites; E, EXample of long accp–s of the p–roW on Abd. III–IV; F, Lateral microsensilla (ms) and al–s of Th. II; G, EXample of long tubular accp–s of the p–roW on Abd. V; H, Ant. I lateral microsensilla (ms). Scale bars: 10 µm (A–E), 5 µm (F). : Published as part of Fanciulli, Pietro Paolo, Leo, Chiara, Convey, Peter, Frati, Francesco & Carapelli, Antonio, 2018, Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae), pp. 392-400 in Zootaxa 4392 (2) on page 398, DOI: 10.11646/zootaxa.4392.2.11, http://zenodo.org/record/1195334